General work stress and suicide cognitions in health-care workers: mediating effect of hopelessness and job satisfaction - Sarigül, Abdulselami; Kaya, Alican; Aziz, Izaddin Ahmad; Yıldırım, Murat; Özok, Halil Ibrahim; Chirico, Francesco; Zaffina, Salvatore (Frontiers in Public Health, 2023)
Individuals with a satisfactory level of job satisfaction are much less likely to feel hopeless about their future and are more likely to perform efficiently in the workplace. General work stress (i.e., the work-related stress subjectively experienced) is a significant predictor of suicide cognitions. Furthermore, it has been posited that satisfaction and hope are fundamental to life from an existential perspective. We, therefore, tested a hypothetical model of general work stress, suicide cognitions, hopelessness, and job satisfaction. The data were collected from 416 health-care workers through a convenience sampling method. The mediation analysis results revealed significant negative and positive relationships among general work stress, suicide conceptions, hopelessness, and job satisfaction. The findings indicate that hopelessness and job satisfaction have a parallel mediating effect in the relationship between general work stress and suicide cognitions. The result of the study is of great importance, which suggests that interventions to alleviate hopelessness and work stress and to boost the job satisfaction of medical staff may help prevent suicide cognitions.